2019
DOI: 10.1093/mnrasl/slz114
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between supermassive black holes, hot atmospheres, and the total masses of early-type galaxies

Abstract: We present a study of relations between the masses of the central supermassive black holes (SMBHs) and the atmospheric gas temperatures and luminosities measured within a range of radii between R e and 5R e , for a sample of 47 early-type galaxies observed by the Chandra X-ray Observatory. We report the discovery of a tight correlation between the atmospheric temperatures of the brightest cluster/group galaxies (BCGs) and their central SMBH masses. Furthermore, our hydrostatic analysis reveals an approximately… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 54 publications
3
31
0
Order By: Relevance
“…It has been suggested that SMBH properties are fundamentally linked with the mass of the host halo [74,75], and that the M BH − L K and M BH − σ v relations arise as a byproduct from the scaling relations between halo mass and optical galaxy properties. Several recent studies seem to confirm that the mass of the central SMBH is more tightly related to the temperature of the host gaseous halo, i.e., the global gravitational potential and hot-halo processes [76][77][78]. We discuss this point, in detail, in Section 5.3.…”
Section: Co-evolution Between Black Hole Mass and Galaxy Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been suggested that SMBH properties are fundamentally linked with the mass of the host halo [74,75], and that the M BH − L K and M BH − σ v relations arise as a byproduct from the scaling relations between halo mass and optical galaxy properties. Several recent studies seem to confirm that the mass of the central SMBH is more tightly related to the temperature of the host gaseous halo, i.e., the global gravitational potential and hot-halo processes [76][77][78]. We discuss this point, in detail, in Section 5.3.…”
Section: Co-evolution Between Black Hole Mass and Galaxy Propertiesmentioning
confidence: 83%
“…However, it is still unclear whether the optical scaling relations of SMBH are fundamental or derive from correlations with other key quantities. Recent findings have instead unveiled that the SMBH masses are more tightly correlated with the properties of the host X-ray gaseous halos, especially in the IGrM regime [76][77][78]. In Figure 16, we summarize our current knowledge of the relation between SMBH mass and X-ray temperature within the core of galaxy groups (R < ∼ 0.15 R 500 ).…”
Section: Co-evolution Between the Igrm And The Central Agnmentioning
confidence: 97%
“…Regarding the radial trends found in TNG, the analysis of the relatively small sample of BCGs from Lakhchaura et al (2019) indicates that the scatter in the MBH − TX relation (∼ 0.26 dex) does not change significantly between Re and 5Re. On the other hand, the data from Gaspari et al 2019 suggest that the MBH − TX relation at cluster core scale (∼ 0.1R500c) has larger intrinsic scatter compared to the one within a smaller galactic/CGM scale, 0.25±0.02 versus 0.21±0.03, i.e.…”
Section: Comparison With X-ray Observationsmentioning
confidence: 92%
“…Bharadwaj et al [17] also found that brightest group galaxies have a higher stellar mass than brightest cluster galaxies, suggesting that there is less gas available to feed the SMBHs. Recent results suggest that the IGrM and intracluster medium (ICM) are also providing a source of gas which feeds and grows the central SMBHs, in particular leading to novel scaling relations between the SMBH mass and the X-ray properties of their host gaseous halos (e.g., Bogdán et al [19], Gaspari et al [20], Lakhchaura et al [21]). These findings imply an interplay between the feedback mechanisms connected with the SMBHs and the macro-scale halos, which could explain some features of cosmological simulations driving a relative break of the L x -T x and L x -M relations at low temperatures (e.g., McCarthy et al [14], Sijacki et al [22], Puchwein et al [23], Fabjan et al [24], Le Brun et al [25]).…”
Section: Galaxy Groups and Astrophysicsmentioning
confidence: 99%